Bumpless transfer control for switched positive linear systems with L1-gain property. (August 2019) - Zhao, Ying; Zhao, Jun; Fu, Jun
Abstract: This study concentrates on the problem of bumpless transfer control for a category of switched positive linear systems with L 1 -gain property. The objective is to reduce the control bumps at switching instants and to maintain the L 1 -gain property as well. For a system in this category with pre-designed controllers, a controller gain interpolation technique is employed to realize the bumpless transfer control. Under the bumpless transfer controllers, the system can satisfy the L 1 -gain property for any switching rules with a dwell time restraint. For the general case, that is, the controllers are to be designed, the bumpless transfer performance is described by a magnitude constraint on the control signal. By co-design of the controllers and switching scheme, we solve the issue of bumpless transfer control for the system with L 1 -gain property, even if the problem of the subsystems is unsolvable. Also, a sufficient condition ensuring the bumpless transfer performance and the L 1 -gain property is obtained. Finally, via controlling a turbofan model, we illustrate the effectiveness of the presented control strategies.